Assessing the impact of COVID-19 on rural women and men in the Niger - Food and Agricultural Organization of the United Nations; United States Agency for International Development; International Food Policy Research Institute; Bryan, Elizabeth; Mawia, Harriet; Ringler, Claudia (Food and Agricultural Organization of the United Nations, 2021)
In response to the first case of COVID-19 in Niger on March 19, the government announced a state of emergency on March 27, 2020. Restrictions were gradually lifted starting in May 2020. The spread of COVID-19 in Niger has been limited. To understand the gendered impacts of the pandemic, phone surveys with rural women and men in Niger were conducted. The study was conducted in 8 regions of the country: Agadez, Diffa, Dosso, Maradi, Niamey, Tahoua, Tillaberi, and Zinder. A sample was drawn from a series of previous surveys that had collected phone numbers. Four rounds of the phone survey were conducted in October 2020, December 2020, February 2021, and April 2021. The surveys focused on the economic impact, coping strategies, impact on food security and dietary diversity and the impact on children’s education and care burden. This brief presents the findings.